PEMAHAMAN DASAR DALAM HUKUM ADAT - Alfatoni, Muhammad Aqil; Alfariel, Enru Achmad; Abidin, Farah Arthanevia; Wardana, Mahendra Kartika (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Indonesia is a country with a very large diversity of indigenous tribes, and in each indigenous tribe in each region there are differences in the laws used in dealing with problems that occur in the respective regions of the indigenous tribe. The large number of indigenous tribes in each region gave rise to this article to provide practitioners with an understanding of fundamental knowledge about customary law in the territory of Indonesia. This study uses a juridical-normative method with a conceptual approach and a study of laws and regulations. The results of this study emphasize the importance of understanding the concept and definition of customary law itself. In addition, this article also highlights that customary law communities still maintain the validity of customary law until now because they believe that decisions made through customary justice mechanisms against a violation are able to present a sense of justice. Not only that, customary justice is also considered capable of restoring social and spiritual balance that is disturbed due to customary violations. And also with the many cultural diversities in Indonesia, it also provides differences related to the understanding or definition of customary law in each region, so that in this article there is how to define customary law in the Bugis and Minangkabau regions. Of course, both regions also provide different definitions regarding what customary law is and also in the process of forming customary law itself there are several stages which are also discussed in this writing.